(untitled) (Modern education and development, 2025)
This article explores effective strategies for developing speaking skills in kindergarten-aged children. Early childhood is a critical period for language acquisition, and oral language development serves as the foundation for literacy and academic success. The article examines factors that influence speaking development, methods and techniques for enhancing verbal expression, and the role of teachers and the learning environment in fostering communicative competence among young learners.